The Mood And Modality In The Second Presidential Debate Between Donald Trump Vs Hillary Clinton - Dwifitri, Rianda (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2023)
This study analyzed the mood and modalities in Donald Trump and Hillary Clinton speech. The objectives of this study were to find out the types mood and modality occur in transcript of the second presidential debate between Donald Trump and Hillary Clinton. This research applied descriptive qualitative research. The data were taken from the transcript of debate. The data source is taken mood and modality appearing in each clause in transcript debate. It data of the research were of sentence contain mood and modality. The findings are showed 237 clauses used modalities and 23 clauses used mood. In the study, there are four types of modalities (47.2% probability, 16.5% usuality, 34.6% Obligation and 1.7% inclination). And there are three types of mood (8.7% Imperative mood, 56.5% Declarative mood, 34.8% Interrogative mood). From this research, the suggestion is for English learners to study and understand mood and modality in order to avoid misunderstanding between English users. Next, teachers should introduce and explain mood and modality as clearly as possible because mood and modality are always used in producing utterance and composition. And the next for research, hopefully there is an analysis about modality taken from other source and analyzing mood and modality. The most dominant types of mood and modalities found in Donald Trump and Hillary Clinton speech is probability (47.2%), and Declarative mood (56,5%).